Nosocomial Disease Risk Management Through the Opti-mization of Mental Health and Learning Capacity among Health Education Students - Agustina Bangun; Luthfiah Mawar; M. Agung Rahmadi; Helsa Nasution; Nurzahara Sihombing; Sarah Milah Ulfa Tanjung; Sopian Ilyas; Jamiluddin Marpaung; Nuraini Nuraini (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
This meta-analytic study aims to comprehensively examine the relationship between mental health, learning capacity among health education students, and competencies in nosocomial disease risk management through cross-contextual empirical synthesis. An analysis of 47 studies involving 12,847 participants from 15 countries demonstrates a strong, statistically significant association between students' mental health and competencies in nosocomial infection prevention, as reflected by a correlation coefficient of r=0.68 (p<0.001) and a 95% confidence interval of 0.61-0.74. Students with high mental health scores (M=78.4; SD=8.2) exhibited substantially superior understanding of infection prevention protocols, namely 43% higher than the control group (M=54.7; SD=12.1; t(846)=18.42; p<0.001; d=2.31). Structural equation modeling confirmed learning capacity as a significant partial mediator (β=0.52; p<0.001), with an indirect effect reaching 35.4% and a 95% CI range of 28.6-42.1%. Mindfulness-based psychoeducational interventions were shown to enhance nosocomial risk identification abilities by 38.7% (F(2,564)=42.18; p<0.001; η²=0.41) while reducing clinical anxiety by 31.2% (t(382)=9.84; p<0.001). These findings extend the frameworks proposed by Song (2024) and Schutte et al. (2025), which primarily emphasize cognitive aspects, by demonstrating that the integration of psychological dimensions yields a multidimensional predictive model explaining 64.3% of the variance in risk management competence (R²=0.643; F(5,841)=304.76; p<0.001), surpassing conventional models that account for only 38-45% of the variance.